Phylogenetic relationships among different breeds of domestic chickens in selected areas of Peninsular Malaysia using RAPD markers - Jayaraj V.K; Yap Fook Choy (2011)
The present investigation was carried out to determine the phylogenetic relationships among different breeds of domestic chickens in selected areas of Peninsular Malaysia. Four RAPD primers were used to characterise the genetic similarity among twenty-seven chicken samples from Peninsular Malaysia. Phylogenetic analysis, using neighbour-joining (NJ), generally produced six clusters which were completely distinguished based on the locality of the chickens. A comparatively high level of genetic variation was observed among the village chickens from different locations. A high level of genetic variation was also observed between commercial broiler chicken from selected localities in Peninsular Malaysia and between the commercial broiler and layer chicken in Peninsular Malaysia. Hence, the results indicated the effectiveness of RAPD to detect similarity between chicken lines and their applicability in establishing genetic relationships among chicken populations